SOME ASPECTS OF ORGANISING SUPERVISION OVER ARTIFICIAL SOURCES OF IONIZING RADIATION IN CHELYABINSK REGION - A. I. Semenov; L. L. Dubrovskaya (Радиационная гигиена)
In experiments on rats (290 animals ) exposed to chronic gamma-radiation in the total dose of 10.0 Gy it was detected that prescription of synthetic harmaceutical of the dihydropyridine class-glutapyrone-together with drinking water during 6 months reduced the rate of malignant neoplasms from 26,5% in the control roup to 13% in the treated animals. In radiation-exposed rats that received lutapyrone there was a narrowing of spectrum of the emerged neoplasms (connectively-tissual tumors only) as compared to the animals of the radiated control group, where blastomas of epithelium and lymphoid origin were also revealed. Low toxicity of lutapyrone and its anticarcinogenic action show the possibility of practical application of preparation for prevention radiation carcinogenesis.